Phenotypical characterization of cassava (Manihot Esculenta Crantz) accessions in Cameroon’s mono-modal rainforest zone - A., Heu; S.B., Mboussi; N.A.N., Kone; A.F., Ngome; J.P., Ngoh Dooh; H., Tekeu; T.W.N., Kuate; Z, Ambang (International Journal of Environment, Agriculture and Biotechnology, 2021)
One hundred and five (105) accessions of cassava collected in the South West and Littoral Cameroon regions were evaluated on a morphological and epidemiological basis. The objective was to study the phenotypic diversity of accessions and its structure based on variables selected among the cassava (Manihot esculentaCrantz) descriptors. Descriptive analysis showed significant phenotypic differences for the traits. Principal component analysis confirmed this important morphological variability. The hierarchical ascending classification made it possible to structure the accessions into 6 and 4 groups. In Ekona, group I consists of accessions with high incidence (IN = 54.03 ± 20.41), group II contains high height (H = 2.01 ± 0.41m), group IV consists of accessions with high severity (SE = 40.44 ± 11.68), petiole length (LP = 39.66 ± 0.03), lobe length (LL = 19.00 ± 0.2 cm) and lobe number (NL = 7.66 ± 0.2).In Njombé, group I consists of accessions with a high incidence (IN = 59.31 ± 20.38), lobe length (LL = 18.08 ± 1.00 cm) and considerable lobe number (NL = 7.44 ± 0.2). These groups offer a wide range of broodstock choices for the creation of improved cassava varieties with interesting potential and adapted to these agro-ecological zones.